PENAMBAHAN PELATIHAN LARI AEROBIK, BACK-UP DAN SIT-UP PADA PELATIHAN SKILL LEBIH MENINGKATKAN ELO RATING - Hairudin -; I Putu Gede Adiatmika; Ketut Tirtayasa; I Made Jawi; Made Muliarta; Ni Nyoman Ayu Dewi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Chess is one of games played by two people opposite by moving chessman on chessboard. Chess players should have theory, experience, instructor of chess and maximal physic so can achieve optimal and improve elo rating. Purpose: This research aims to know is: training addition aerobic run, back-up, sit-up on skill training is better to improve elo rating compared to skill training only to chess co-curricular students. Methods: The experimental research is disigned to use the randomized pretes post test control group design. Research sample are chess co-curricular students SMP Negeri 4 Denpasar 32 people. Sample tobe 2 groups, group I is given training airobic run back-up, sit-up, and skill for 6 weeks with training frequency 3 times a week, and group II is given skill training only for 6 weeks with training frequency 3 times a week. Before and after 6 weeks training, all sample follows Switzerland rapid chess championship 5 rounds. Results: Average rate elo rating of 2 groups is analysis. Based on analysis result, is known that average rate elo rating group I before 1198,75 and after training 1235,75, differently in meaning (p < 0,05). Rate of elo rating group II before 1198,75 and after training 1162,88, differently in meaning (p < 0,05). Average elo rating of 2 groups, differently in meaning (p < 0,05). It means training addition aerobic run, back-up, sit-up has improve elo rating. Conclusion: Conclusion is that training addition aerobic run, back-up, sit-up on skill training is better in improving elo rating than skill training on chess co-curricular student.